Pentingnya Kerja Sama dalam Pengorganisasian Perspektif Al-Quran - Muhammad Yudha Ardiansyah; Hamidullah Mahmud (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Organizing is an essential management function, including the division of tasks, delegation of authority, and coordination between members to achieve common goals. The Qur'an emphasizes the principle of unity and order in the organization, as reflected in Surah As-Shaff verse 4 which describes the importance of lining up in unity. In addition, the principle of cooperation (ta'awun) is also described in Surah Al-Ma'idah verse 2, which emphasizes collaboration in goodness and piety. This research is a library research that focuses on the study of the management function of organizing in the Qur'an, which is examined from the perspective of the Experts of the Interpretation of the Qur'an. Thus, this paper aims to show the relevance of the teachings of the Qur'an in building an effective and ethical organization and how these principles can be applied in the context of modern management..